2023
DOI: 10.1371/journal.pone.0280240
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hearing protection devices on spatial awareness in complex listening environments

Abstract: Hearing protection devices (HPDs) remain the first line of defense against hazardous noise exposure and noise-induced hearing loss (NIHL). Despite the increased awareness of NIHL as a major occupational health hazard, implementation of effective hearing protection interventions remains challenging in at-risk occupational groups including those in public safety that provide fire, emergency medical, or law enforcement services. A reduction of situational awareness has been reported as a primary barrier to includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
1
5
0
1
Order By: Relevance
“…This is consistent with findings showing that military personnel were concerned about using HPDs because of reductions in situational awareness, interference in detection and localization of auditory cues, and because of incompatibility with other military gear [42]. Furthermore, recent evidence demonstrated that the use of HPDs does disrupt spatial hearing, specifically in localization performance and in monitoring speech signals [43]. Overall, HPDs are often avoided because they cause an increase in listening effort, variability in sound-localization ability, and reduction of effective communication [42][43][44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with findings showing that military personnel were concerned about using HPDs because of reductions in situational awareness, interference in detection and localization of auditory cues, and because of incompatibility with other military gear [42]. Furthermore, recent evidence demonstrated that the use of HPDs does disrupt spatial hearing, specifically in localization performance and in monitoring speech signals [43]. Overall, HPDs are often avoided because they cause an increase in listening effort, variability in sound-localization ability, and reduction of effective communication [42][43][44].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, recent evidence demonstrated that the use of HPDs does disrupt spatial hearing, specifically in localization performance and in monitoring speech signals [43]. Overall, HPDs are often avoided because they cause an increase in listening effort, variability in sound-localization ability, and reduction of effective communication [42][43][44]. Adoption and acceptance of HPDs in the fire service continue to be low [45], despite longstanding efforts to address hazardous noise in occupational groups [1,46,47] and, in particular, the fire service [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…HPDs can attenuate situational awareness, which may reduce compliance to using them as standard personal protective equipment. ( Snapp et al, 2023 ). Various promising pharmacologic agents have also been identified for NIHL intervention, including antioxidants ( Bielefeld et al, 2007 ; Campbell et al, 2011 ; Fetoni et al, 2013 ), glutamate antagonists ( Hu et al, 2020 ), cell death regulators ( Wilson et al, 2014 ), and anticonvulsive drugs ( Bao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Specifically, unmanaged chronic auditory loss may predispose to learning, language, and psychosocial maldevelopment; voice quality impairment; tinnitus; dementia; and self-harm due to a reduced capability of situational awareness. 2,3 Thus, efforts to improve hearing competence may mitigate pathophysiologic decline and may be warranted. A variety of modalities are available to regain partial to complete hearing proficiency, involving nonsurgical options with use of hearing aids and assistive listening devices, and surgically-implanted devices, particularly cochlear implants and auditory brainstem implants.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury outcomes may range from complete recovery to persistent cognitive, systemic, neuromuscular, and neurosensory deficits 1 . Specifically, unmanaged chronic auditory loss may predispose to learning, language, and psychosocial maldevelopment; voice quality impairment; tinnitus; dementia; and self‐harm due to a reduced capability of situational awareness 2,3 . Thus, efforts to improve hearing competence may mitigate pathophysiologic decline and may be warranted.…”
Section: Introductionmentioning
confidence: 99%